DETERMINAN YANG MEMPENGARUHI KUALITAS INFORMASI AKUNTANSI: STUDI EMPIRIK PADA PERUSAHAAN SEKTOR UTAMA SUBSEKTOR PERTANIAN TAHUN 2011-2016 - Indrasti, Anita Wahyu; Sunarwibowo, Rizki Pratomo; Lestari, Indah Rahayu (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to determine which variables affect the quality of accounting information. Company Ownership, leverage, profitability, audit committee, and dividend policy variables are used as independent variables, as well as company size and sales growth as controlling variables. This study uses FGLS (feasible generalized least squares) and STATA / MP 13.0 applications to estimate panel data models. The results of the study revealed that profitability, audit committee and dividend policy partially influence the quality of accounting information, while company ownership, leverage does not affect the quality of accounting information Keywords: accounting information quality, company ownership, profitability, audit committees, dividend policy